(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The nature of the relationship between passions and reason is an issue that plays a key role in the ancient ethical discussions. After Plato, stressing out the reasonable against the affective part of the soul becomes a dominant stream within these discussions. In the stoic philosophy, the relationship between reason and passions has specific nature. There are no rational and irrational parts in the soul; instead, passions are error of the rational part. Thus, according to the Stoics, the reason is the only and necessary capacity for virtuous behavior and only those who act reasonably are virtuous men. For them, only the reason can ensure “life in accordance with nature ” - the stoic ethical imperative. The therapeutic role of stoic ethics, which consists of rational overcoming of passions, serves as an inspiration for contemporary ethics and psychotherapy. After the analysis of the basic implications of the connection between passions, reason and therapy in the stoic ethics, in this article we will analyze these implications in contemporary ethics and the possibility of the appropriate application of the stoic therapeutic precepts in contemporary context.